The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.17503/agrivita-2014-36-1-p065-071
|View full text |Cite
|
Sign up to set email alerts
|

Biochar Effect at Potassium Fertilizer and Dosage Leaching Potassium for Two-Corn Planting Season

Abstract: An experiment in greenhouse was conducted to study the effect of biochar and fertilizer potassium against leaching and uptake of potassium on the growth of maize during the two cropping seasons. In the experiment, a randomized block design with seven treatments and three-time replication was applied, namely control (without biochar and KCl), biochar (30 t ha

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 3 publications
1
21
0
2
Order By: Relevance
“…Biochar seems to be one of the most effective materials reducing soil K losses in regions with high rainfall (Widowati and Asnah 2014). Several studies reported soil exchangeable K increase after biochar application.…”
Section: Biochar and Soil Chemical Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Biochar seems to be one of the most effective materials reducing soil K losses in regions with high rainfall (Widowati and Asnah 2014). Several studies reported soil exchangeable K increase after biochar application.…”
Section: Biochar and Soil Chemical Propertiesmentioning
confidence: 99%
“…Several studies reported soil exchangeable K increase after biochar application. This impact was in part due to a direct supply of K from biochar (Zong et al 2016) or by indirect improvement in fertilizer use efficiency by adsorption of nutrients on exchange surfaces thus reducing leaching loss (Widowati and Asnah 2014).…”
Section: Biochar and Soil Chemical Propertiesmentioning
confidence: 99%
“…Application of biochar increased 54,78% water storage, while that without biochar application was 50.86%. As reported by Widowati and Asnah (2014) leaching of K from litter biochar affected the amount of water drained which tended to decrease with increasing rates of biochar. The use of biochar can improve soil porosity (Widowati et al, 2012;Steiner et al, 2007).…”
Section: Soil Water Contentmentioning
confidence: 60%
“…However, under tropical conditions, organic matter is rapidly oxidized and added bases are rapidly leached (Tiessen et al, 1994). On the other hand, application of biochar has been proved to reduce nutrient leaching (Downie et al, 2009), and after incorporation into soil, biochar improves soil fertility (Lehmann et al, 2003;Steiner et al, 2007), increase the efficiency of N fertilizer (Widowati et al, 2012), and reduce the use of K fertilizers in Inseptisols (Widowati and Asnah, 2014). Biochar as a soil amendment is potential for improving crop yields and quality of degraded soils.…”
Section: Introductionmentioning
confidence: 99%
“…N, P and K. When these wastes are used to produce biochar, they bring about an opportunity to be used as a sustainable soil amendment. It may help to avoid further reduction of soil organic carbon (Gaskin et al, 2008) and prevent increased fertilizer-use (Widowati and Asnah, 2014). Pyrolysis is the combustion of organic waste materials in complete absence or partial presence of oxygen, leading to the formation of carbon-rich char (biochar) (Thies and Rillig, 2009).…”
Section: Introductionmentioning
confidence: 99%